Working Poverty in Europe
XX, 342 p.
Keywords: Offering a comparative perspective, this book examines working poverty - those in work who are still classified as 'poor'. It argues that the growth in numbers of working poor in Europe is due to the transition from a Keynesian Welfare State to a 'post-fordist' model of production.